Determination of Semivolatile Organic Nitrates in Ambient Atmosphere by Gas Chromatography/Electron Ionization–Mass Spectrometry - Rui Li (Atmosphere, 2019)
Semivolatile organic nitrates (SVONs) contribute a large proportion of total organic nitrates and play an important role in the tropospheric chemistry. However, the composition and concentrations of SVONs in the atmosphere remain unclear due to the lack of reliable analytical techniques for specific organic nitrates. In this study, a method based on gas chromatography and electron ionization⁻mass spectrometry was developed to detect ambient SVONs that were collected via polyurethane foam disk enrichment. Three SVONs were identified in the semivolatile samples from urban Jinan during spring based on the characteristic fragment ions of [NO2]+ and [CH2NO3]+ and the characteristic fragment loss of NO2 and NO3: 1-pentyl nitrate (molecular weight [MW] = 133), 4-hydroxy-isoprene nitrate (MW = 147), and (3,4)-di-hydroxy-isoprene nitrate (MW = 163). The latter two isoprene nitrates were rarely detected in the real atmosphere in previous studies. The contents of 1-pentyl nitrate, 4-hydroxy-isoprene nitrate, and (3,4)-di-hydroxy-isoprene nitrate were roughly quantified based on the standard of 1-pentyl nitrate, with a detection limit of 50 μg L−1. In addition, Fourier transform infrared spectrometry was used to determine the total SVONs content. The average concentrations of 1-pentyl nitrate, 4-hydroxy-isoprene nitrate, (3,4)-di-hydroxy-isoprene nitrate, and total SVONs in Jinan during spring were 20.2 ± 7.2, 13.2 ± 7.2, 36.5 ± 8.4, and 380.0 ± 190.8 ng m−3, respectively. The three identified SVONs contributed only 20.2 ± 5.5% to the total SVONs, which suggests that some unidentified SVONs are present in the ambient atmosphere and that studies with improved or advanced analytical techniques will be required to identify them.